A Comprehensive Study on Biochar-Based Nanocomposites in Removal of Organic Pollutants from Wastewater - Nandkishor Lodhi; Santosh Narayan Chadar; Deshraj Singh Thakur; Ashish Raikwar (Journal of Water and Environmental Nanotechnology)
Biochar is a carbon-rich material created by heating organic biomass like wood, crop leftovers, or animal waste in a low-oxygen environment through pyrolysis. Its use in agriculture and environmental practices is widespread due to its ability to enhance soil fertility, store carbon, and lower greenhouse gas emissions. Biochar nanocomposites are being explored for their potential to enhance properties and expand applications through combinations with various nanomaterials, engineered at the nanoscale. Factors including urbanization, economic growth, and population increase contribute to rising levels of wastewater pollution globally. Therefore, before disposal or reuse, wastewater must undergo treatment to remove organic pollutants, a complex task that involves identifying and eliminating new or unidentified contaminants using advanced equipment and methods. The use of biochar in wastewater treatment is seen as a solution to the harmful effects on living organisms caused by traditional methods like ozonation, hydrogen peroxide, and chlorine dioxide when removing organic pollutants.